The Quality of English Learning at Home: A Case Study of Three Years Old Indonesian Young Learner - Pasiningsih (Universitas Negeri Jakarta, 2025)
Parental involvement in introducing English at the early childhood education (ECE) level has been increasingly recognized for its positive impact. However, concerns raised regarding the quality of English learning provided at home, especially in the Indonesian context where research has primarily focused on teachers rather than parents. This study aims to explore the quality of English learning at home facilitated by parents of a three-year-old child. A qualitative case study method was employed, with data collected through three sessions of home observations involving painting and shared book reading activities. The analysis followed the Miles and Huberman (1994) model, comprising data reduction, data display, and conclusion drawing. The findings reveal that parents successfully integrated the child's interests (e.g., painting and animals) into English learning, fostering positive interaction and engagement. However, certain practices were less effective, such as the use of overly simple and close-ended questions, and a parental tendency to dominate the learning process, limiting the child's active participation and critical thinking development. While parents play a vital role in early English learning at home, the quality of instruction can be improved. ECE teachers are encouraged to support parents through workshops or parenting events that focus on effective questioning strategies, scaffolding techniques, and ways to foster child-led learning experiences.